(untitled) (Jurnal Matematika, Statistika dan Komputasi, 2022)
This paper is aimed to the notion of θ-φ-contraction defined on a metric space with w-distance. Moreover, fixed point theorems are given in this framework. Some illustrative examples are provided to advocate the usability of our results. As an application, we prove the existence and uniqueness of a solution for the nonlinear Fredholm integral equations.